The Influence of Workload and Work Stress on Turnover Intention Mediated by Job Satisfaction (A Study at Harapan Hospital Magelang) - Munawar Munawar; Tristiana Rijanti (Mandalika Institute, 2025)
Based on the research conducted at RS Harapan Magelang, this study investigates the impacts of workload and work stress on job satisfaction and turnover intention. The research employed a quantitative approach, utilizing data gathered through questionnaires administered to nurses and midwives. The findings show that workload and work stress do not significantly affect job satisfaction, with statistical results indicating no substantial relationships. Additionally, the study reveals that work stress positively and significantly impacts turnover intention, suggesting that higher stress levels lead to a stronger desire to leave the job. However, job satisfaction does not mediate the relationship between workload or stress and turnover intention. This highlights the importance of addressing stress management in the workplace to reduce turnover and improve employee retention. The results provide valuable insights for organizational strategies aiming to enhance employee well-being and decrease turnover rates.